2024
DOI: 10.1038/s41598-024-57024-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oral cancer properties of potential probiotic lactobacilli isolated from traditional milk, cheese, and yogurt

Yousef Nami,
Omid Tavallaei,
Amir Kiani
et al.

Abstract: This study investigates the probiotic and anti-cancer effects of 21 isolated Lactobacillus strains from cheese, milk, and yogurt in Kermanshah, Iran, on oral cancer cell lines KB and OSCC. Four selected isolates (Y33, M45, C5, and C28) displayed good viability and resistance to specific antibiotics. Notably, strains C28 and Y33 exhibited the best results, showing susceptibility or semi-susceptibility to five antibiotics. Y33, with high cell surface hydrophobicity (62%), demonstrated significant anti-pathogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…These findings were based on phenotypic and sequencing analyses. Early research has led to the strong notion that dairy products, such as milk, yogurt 28 , 29 , cheese and sourdough 30 , 31 are the primary source of Lactococcus sp . Nonetheless, accumulating evidence from multiple studies has demonstrated the isolation of Lactococcus species from non-dairy sources such as fresh vegetables 32 , fruits 33 , leaves 34 , and silage 35 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings were based on phenotypic and sequencing analyses. Early research has led to the strong notion that dairy products, such as milk, yogurt 28 , 29 , cheese and sourdough 30 , 31 are the primary source of Lactococcus sp . Nonetheless, accumulating evidence from multiple studies has demonstrated the isolation of Lactococcus species from non-dairy sources such as fresh vegetables 32 , fruits 33 , leaves 34 , and silage 35 .…”
Section: Discussionmentioning
confidence: 99%